Model Pembelajaran Berbasis STEM untuk Meningkatkan Pemahaman Konsep Termodinamika dalam Fisika - Alam Senopati; Arya Mahardika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the effectiveness of STEM (Science, Technology, Engineering, and Mathematics)-based learning models in improving students' understanding of thermodynamic concepts. The research method used is a quasi-experimental with a pretest-posttest design. The subjects of the study were high school students who were divided into experimental and control classes. The results showed that the STEM approach can significantly improve students' conceptual understanding and problem-solving skills compared to conventional learning models. The implication of this study is the need for integration of the STEM approach in physics learning in order to improve the quality of education in the modern era.